2016
DOI: 10.1016/j.lindif.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Alphanumeric and non-alphanumeric Rapid Automatized Naming in children with reading and/or spelling difficulties and mathematical difficulties

Abstract: Although poor Rapid Automatized Naming (RAN) is a risk factor for reading and/or spelling difficulties (RSD) as well as for mathematical difficulties (MD), many questions surround this relationship. The main objective of the present study was to obtain insight in the relationship between alphanumeric vs. non-alphanumeric RAN and reading/spelling and mathematics in groups of 7-to-10-year-old children with RSD, MD, both RSD + MD, and in typically developing (TD) children. Analyses of variance between the groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 60 publications
7
55
0
2
Order By: Relevance
“…Wilson et al (2015) examined RAN performance among RD and MD adults and found similar deficits in both groups. Two recent studies found RAN deficits in children with both MD and RD (Donker, Kroesbergen, Slot, Van Viersen, & De Bree, 2016;Slot et al, 2016). Moreover, other studies found that RAN deficit was a shared risk factor between ADHD and reading (McGrath et al, 2011;Shanahan et al, 2006).…”
Section: The Role Of Perception Speed In Mathematics Abilitiesmentioning
confidence: 97%
“…Wilson et al (2015) examined RAN performance among RD and MD adults and found similar deficits in both groups. Two recent studies found RAN deficits in children with both MD and RD (Donker, Kroesbergen, Slot, Van Viersen, & De Bree, 2016;Slot et al, 2016). Moreover, other studies found that RAN deficit was a shared risk factor between ADHD and reading (McGrath et al, 2011;Shanahan et al, 2006).…”
Section: The Role Of Perception Speed In Mathematics Abilitiesmentioning
confidence: 97%
“…We opted for inclusion of alphanumeric RAN only as we wanted to assess the specific phonology and orthography association. Furthermore, it has been reported that nonalphanumeric RAN does not relate to spelling (Donker, Kroesbergen, Slot, van Viersen, & de Bree, 2016). A longitudinal study of both nonalphanumeric and alphanumeric RAN is required to gain more insight into the general and specific contributions of RAN to spelling.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Yet another explanation for nonalphanumeric RAN being slower is because it requires an extra processing step. In addition to the processes underpinning RAN in general (Donker, Kroesbergen, Slot, Van Viersen, & De Bree, ; Georgiou et al, ), nonalphanumeric RAN is assumed to require access to semantic information, whereas alphanumeric RAN does not. Yet, when Cummine et al () examined RAN performance from a neurological perspective by using functional magnetic resonance imaging (fMRI), they found that RAN objects activated fewer regions than RAN digits and letters did.…”
Section: Introductionmentioning
confidence: 99%